DiRPL: A RPL-Based Resource and Service Discovery Algorithm for 6LoWPANs - Luca Davoli; Mattia Antonini; Gianluigi Ferrari (Applied Sciences, 2018)
The Internet of Things (IoT) will bring together billions of devices, denoted as Smart Objects (SOs), in an Internet-like architecture. Typically, SOs are embedded devices with severe constraints in terms of processing capabilities, available memory (RAM/ROM), and energy consumption. SOs tend to be deployed in environments in which the human intervention is not suitable or needs to be minimized (e.g., smart city maintenance). They must adapt to the surrounding environment by self-configuring: to this end, several mechanisms have been proposed (e.g., UPnP, ZeroConf, etc.). In this paper, we focus on IEEE 802.15.4 networks with IPv6 over Low-Power Wireless Personal Area Network (6LoWPAN) adaptation layer, where IPv6 Routing Protocol for Low-Power and Lossy Networks (RPL) is the routing protocol of choice. In this context, we propose a lightweight RPL-based mechanism to Resource Discovery (RD) and Service Discovery (SD), denoted as DiRPL. In particular, DiRPL exploits the RPL handshake to detect new nodes in the network; resources are then simply discovered with a Constrained Application Protocol (CoAP) request and can thus be published in a local resource directory. A very attractive feature of the proposed DiRPL approach is that it builds on well-defined and well-known standard protocols. The performance of the proposed system is investigated with WisMote nodes deployed inside the Cooja simulator, running the Contiki operating system. Practical application scenarios to large-scale smart city monitoring, such as smart lighting and large-scale water consumption monitoring, are investigated.